Living with cancer in the COVID‐19 pandemic: An Italian survey on self‐isolation at home. (7th December 2020) - Biagioli, Valentina; Albanesi, Beatrice; Belloni, Silvia; Piredda, Alessio; Caruso, Rosario
Abstract: Objective: To investigate the perception of self‐isolation at home in patients with cancer during the lockdown period resulting from the COVID‐19 outbreak in Italy. Methods: A cross‐sectional descriptive study was conducted through an online survey of patients with cancer who were sheltering at home from 29th March to 3rd May 2020. Perception of self‐isolation was assessed using the ISOLA scale, after evaluation of its psychometric properties. Content analysis was used to analyse two open‐ended questions. Results: The participants were 195 adult patients with cancer (female = 76%; mean age = 50.3 ± 11.2; haematological malignancy = 51.3%). They reported moderate isolation‐related suffering ( M  = 2.64 ± 0.81), problems in their relationships with others ( M  = 3.31 ± 1.13) and difficulties in their relationships with themselves ( M  = 3.14 ± 1.06). Patients who experienced significantly more social problems were older, had less education and were living without minor children. Overall, four main categories emerged from the qualitative content analysis: (1) lack of freedom and social life, (2) uncertainty and worries, (3) feeling supported and (4) dealing with isolation. Conclusion: Living with cancer in the COVID‐19 pandemic was often perceived as an isolating experience, primarily in terms of detachment from loved ones.